The Effect of the WebQuest Strategy on the Academic Achievement of First-Grade Intermediate Students in Chemistry." (Journal of the College of Basic Education, 2025)
this study aimed to investigate the effect of the WebQuest strategy on the achievement of first-grade intermediate students in Chemistry. This was achieved by testing the null hypothesis, which states:"There is no statistically significant difference at the significance level (a £05)between the mean scores of the experimental group students, who were taught using the WebQuest strategy, and the mean scores of the control group students, who were taught using the conventional method, on the Chemistry achievement test."The researcher adopted a quasi-experimental design with a post-test for two independent, equivalent groups. The research population comprised (3543) first-grade intermediate students in Baghdad/Karkh First Governorate schools for the academic year (2024-2025). A random sample of (60) students was selected from this population. Section (A) was assigned as the experimental group (N=30), which was taught using the WebQuest strategy, while Section (B) was assigned as the control group (N=30), which was taught using the conventional method. The equivalence of the two groups was verified before commencing the experiment. Research instruments included the preparation of (95) behavioral objectives for the fourth chapter of the first-grade intermediate Chemistry textbook (Chemical Reactions and Their Representation) and the development of (12) lesson plans for each group. The researcher taught both groups during the research implementation period.Data analysis results revealed statistically significant differences at a significance level of (α ≤ 0.05) between the mean scores of the experimental group students (M=35.621, SD=1.896) and the mean scores of the control group students (M=20.845, SD=7.875) on the Chemistry achievement test, in favor of the experimental group.These findings indicate a positive effect of the WebQuest strategy on Chemistry achievement among first-grade intermediate students. Based on these results, the researcher recommended the necessity of using the WebQuest strategy in teaching various science subjects, effectively integrating active learning strategies, including WebQuest, into intermediate stage curricula, and training teachers on the use of these modern strategies.